2016
DOI: 10.1016/j.ijheatmasstransfer.2016.03.088
|View full text |Cite
|
Sign up to set email alerts
|

Liquid temperature dependence of kinetic boundary condition at vapor–liquid interface

Abstract: For the accurate description of heat and mass transfer through a vapor-liquid interface, the appropriate modeling of the interface during nonequilibrium phase change (net evaporation/condensation) is a crucial issue. The aim of this study is to propose a microscopic interfacial model which should be imposed at the interface as the kinetic boundary condition for the Boltzmann equation. In this study, we constructed the kinetic boundary condition for monoatomic molecules over a wide range of liquid temperature b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
19
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 50 publications
(134 reference statements)
2
19
0
Order By: Relevance
“…In our recent studies [24,27], we confirmed that ρv z is well described as a linear function of σ/ρ * and furthermore that β ne and β nc depend only on liquid temperature. When J coll = 0 in Eq.…”
Section: Kinetic Boundary Conditionsupporting
confidence: 77%
See 3 more Smart Citations
“…In our recent studies [24,27], we confirmed that ρv z is well described as a linear function of σ/ρ * and furthermore that β ne and β nc depend only on liquid temperature. When J coll = 0 in Eq.…”
Section: Kinetic Boundary Conditionsupporting
confidence: 77%
“…In this section, we explain the KBC that is established in the vapor-liquid two-phase system with steady net evaporation/condensation [24,27]. As the starting point, we examine a conventional KBC that is expressed as the linear combination of the diffuse reflection and complete condensation conditions [30,31],…”
Section: Kinetic Boundary Conditionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, even the small differences between the experimental conditions (such as chemical impurities on the interface and variation of surface temperatures of liquids being investigated) may have a dramatic effect on the measurement results. The dependence of evaporation and condensation coefficients from the surface temperature is also reported in simulation works (27,28). It was found that those coefficients, which are close to unity at low temperatures, begin to decrease if the surface temperature is increased well above the triple point.…”
mentioning
confidence: 54%